Induction of mitochondrial apoptosis for cancer therapy via dual-targeted cascade-responsive multifunctional micelles. Issue 48 (22nd November 2018) - Wei, Guoqing; Wang, Yi; Huang, Xuehui; Yang, Guang; Zhao, Jingya; Zhou, Shaobing
Abstract : A dual-targeted cascade-responsive multifunctional micelle is fabricated, which can carry the therapeutic agent into the mitochondrion to induce mitochondrial apoptosis. Abstract : Herein, we present a prodrug-loaded multifunctional polymer micelle with hyaluronidase/redox/light multilevel responses and with cell membrane/mitochondrion-dual targeting abilities. This nanocarrier can be internalized by tumor cells via CD44 receptor-mediated targeting. The encapsulated prodrug is released as the carrier is dissociated after the initial degradation of the hyaluronic acid layer by hyaluronidase, followed by the cleavage of the disulfide bonds between hydrophilic and hydrophobic segments in the micelle under the conditions of increased levels of GSH in the cytoplasm. The released prodrug can rapidly target the mitochondria via the TPP function, and convert to the free drug cisplatin through a redox-responsiveness effect. Simultaneously, the membrane permeability of the mitochondria can be improved by the generated reactive oxygen species (ROS) from light irradiation, thus allowing the entry of cisplatin into the mitochondria and causing mitochondrial damage, ultimately leading to mitochondria-mediated apoptosis. Consequently, this nanoformulation shows a highly effective anticancer efficacy in vivo .